Prohibition of Abuse of Law : a New General Principle of EU Law?. - Vogenauer, Stefan (Studies of the OIECL., 2011)
The Court of Justice has been alluding to 'abuse and abusive practices' for more than thirty years, but for a long time the significance of these references has been unclear. Few lawyers examined the case law, and those who did doubted whether it had led to the development of a legal principle. Within the last few years there has been a radical change of attitude, largely due to the development by the Court of an abuse test and its application within the field of taxation. In this book, academics and practitioners from all over Europe discuss the development of the Court's approach to abuse of.